Dostopnost knjižničnih storitev na Obalno-kraškem območju - Malec, Luana (Knjižnica, 2012)
The analysis shows that library services are provided in all municipalities inthe Coastal-Carst region. However, 53,5% or 229 of all Coastal-Karst settlements remain uncovered or inadequately covered by library services, mostly in the area of the Kosovel Libray of Sežana, followed by the Library ofKoper and the Maksa Samsa Library od Ilirska Bistrica. On the other side thefact that only 21,5% of inhabitants are left out of library services is encouraging.
Keywords: demografski podatki; geografski podatki; knjižnične storitve; mreža splošnih knjižnic; obalno-kraško knjižnično območje; Osrednja knjižnica Srečka Vilharja; splošne knjižnice; statistična analiza